Intramolecular vibrational redistribution in the non-radiative excited state decay of uracil in the gas phase: an ab initio molecular dynamics study1. Issue 17 (7th May 2015) - Carbonniere, Philippe; Pouchan, Claude; Improta, Roberto
<x xml:space="preserve">Abstract</x> MD simulations provide the first atomistic insights into the IVR processes of photoexcited uracil soon after ground state recovery.